KORELASI CT SCAN KEPALA DAN ULTRASONOGRAFI SELUBUNG SARAF OPTIK DENGAN SKOR GLASGOW COMA SCALE PADA PASIEN TRAUMA KAPITIS - Pramono, Rufik Tejo; Murtala, Bachtiar; Ilyas, Muhammad (Universitas Udayana, 2023)
Increased intracranial pressure is a complication in patients who experience head trauma. Increased intracranial pressure can cause loss of consciousness and even death. The Glasgow coma scale (GCS) is a rating scale that has a purpose as an assessment of the patient's consciousness. Computed Tomography (CT) Scan is one of the modalities used in head trauma patients to see intracranial lesions as the cause of increased intracranial pressure. Transocular ultrasound can be used to detect elevated intracranial pressure. Changes in the diameter of the optic nerve sheath are directly caused by changes in increased intracranial pressure. This study is a cross-sectional study with patients diagnosed with head trauma who were referred to the Radiology Installation of Dr. Wahidin Sudirohusodo Hospital for CT Scan of the head and transocular ultrasound examination from July to December 2021. All study subjects were assessed for GCS, the appearance of intracranial lesions on examination. CT scan of the head and measurement of the diameter of the optic nerve sheath with transocular ultrasound examination were then analyzed. There were 32 research subjects with head trauma. There is a correlation between the degree of consciousness and the CT scan of the head, namely intracranial hemorrhage and basal cistern compression with p values of 0.045 (r=0.357) and 0.005 (0.480), respectively, while the midline shift and cerebral edema variables have no correlation (p>0, 05). There was a correlation between the degree of consciousness and the diameter of the right and left optic nerve sheaths with p-values of 0.006 (r=-0.472) and 0.011 (-0.442). There was a relationship between the diameter of the right and left optic nerve sheaths and the head CT scan, namely midline shift, cerebral edema and basal cistern compression (p<0.05) while there was no relationship between intracranial bleeding variables (p>0.05). Keywords: CT scan of the head, transocular ultrasound, GCS, head trauma.